Rozwój szkolnictwa dla mniejszości tubylczych na Alasce - Gmerek, Tomasz (Biuletyn Historii Wychowania, 2015)
Development of Education for Indigenous Minorities in Alaska The article deals with the issue of the relation between education and processes of the development of ethnic identity of indigenous minorities in Alaska. Particular emphasis was placed on reconstructing the educational practices and policy that is being implemented for indigenous minorities within the school system (especially assimilation, discrimination and revitalisation of ethnic identity). An attempt was made at examining the relationship between schooling, socialisation, language policy, and the development of aboriginal minorities in Alaska.